Sharing objects in a distributed system. - CAHILL, VINNY (IEEE Computer Society Press, 1993)
This paper presents a design for the use of DSM techniques and system-supported synchronisation to support shared access to persistent objects in a distributed environment. We adopt a hybrid approach where the system granularity is sometimes pages and sometimes objects. We are interested in providing shared access to small (i.e., less than a page) objects in a general purpose, language-independent environment, and supporting both DSM and RPC object access mechanisms. 1 Introduction Object-oriented systems have traditionally relied on remote procedure calls (RPC) as the fundamental method for accessing remote objects in distributed environments. However, the RPC model of shipping invocations to an object can be limiting, preventing, for example, simultaneous legal accesses to copies of an object on multiple nodes.
Proceedings of the 3rd International Workshop on Object Orientation in Operating Systems
3rd International Workshop on Object Orientation in Operating Systems
PUBLISHED
Asheville, NC
Keywords: Computer Science